Measurement of Aquaculture Chemotherapeutants in Flocculent Matter Collected at a Hard-Bottom Dominated Finfish Site on the South Coast of Newfoundland (Canada) After 2 Years of Fallow - Hamoutene, Dounia; Salvo, Flora; Egli, Stefana N.; Modir-Rousta, Ali; Knight, Robyn; Perry, Geoff; Bottaro, Christina S.; Dufour, Suzanne C. (Frontiers in Marine Science, 2018)
The expansion of aquaculture is resulting in sites being installed over a diversity of substrate types, leading to different potential chemotherapeutant degradation scenarios. There is little to no information on the biodegradation and/or persistence of chemotherapeutants at hard-bottom dominated aquaculture sites having little natural sediment. In this study, we measured organic matter (OM) content and concentrations of chemicals linked to finfish aquaculture activities (trace elements, antibiotics and parasiticides) in flocculent matter samples collected close to cages at a site fallowed for two years and at an active site, the latter being indicative of flocculent chemical signature during production. Our results show persistence of flocculent matter after two years of fallow. The chemical signature of the samples confirms that Cu, Zn, Ca and P, present around fish cages, are direct markers of aquaculture wastes. Persistence of two pyrethroids, one avermectin, and one antibiotic in grab samples show a potentially lasting association between these chemicals and the OM from fish feed and wastes, even after two years. Overall, the concentrations measured do not indicate a direct lethal toxicity on marine organisms (as per studies described in literature) except for Zn. Nevertheless, the long-term persistence of a flocculent mixture rich in chemicals and the lack of information on sublethal and synergistic effects on hard-bottom communities calls for caution and additional studies.